The faith of leap : embracing a theology of risk, adventure & courage - Frost, Michael, 1961-; Hirsch, Alan, 1959 October 24- (Grand Rapids, Mich. : Baker Books, 2011)
"So much of our lives is caught up in the development and maintenance of security and control. But as Helen Keller observed, "Security is mostly a superstition. . . . Avoiding danger is no safer in the long run than outright exposure. Life is either a daring adventure or nothing." And when our only experience of Christianity is safe and controlled, we miss the simple fact that faith involves risk. In The Faith of Leap, Michael Frost and Alan Hirsch challenge you to leave the idol of security behind and courageously live the adventure that is inherent in our God and in our calling. Their corrective to the dull, adventureless, risk-free phenomenon that describes so much of contemporary Christianity explores the nature of adventure, risk, and courage and the implications for church, discipleship, spirituality, and leadership" -- BACK COVER.
The end of the beginning : introduction -- The spirit's edge : putting adventure back into the venture -- Jesus is my disequilibrium : where friends become comrades -- A walk on the wilder side : overcoming fear in pursuit of wild hope -- The hero's journey : becoming who we were made to be -- Getting over risk aversion : extracting truth from dare -- Missional catalysis : thinking differently about the church and her mission -- The risk of neighborliness : an invitation to take the plunge -- The beginning of the end : conclusion.
Includes bibliographical references.
Keywords: Mission of the church; Risk-taking (Psychology) -- Religious aspects -- Christianity